2010
DOI: 10.1068/a42122
|View full text |Cite
|
Sign up to set email alerts
|

Actor Networks, Modes of Production, and Waste Regimes: Reassembling the Macro-Social

Abstract: In the past ten to fifteen years, waste scholarship has expanded and deepened: we have seen an increasing number of rich case studies both on waste-related social movements (primarily in the US) and on specific waste materials (for the most part in the UK and Australia). Many of these also experimented with new conceptual frameworks, greatly deepening the theoretical foundations and the interpretive capacities of waste scholarship in the social sciences. Some of these novel approaches focused on microlevel pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 36 publications
1
109
0
6
Order By: Relevance
“…Gille, 2010). For example, researchers have in their quest to understand landfills strongly contributed to consolidating the image of landfills as something negative (Paper II).…”
Section: The Perception Of Landfills As Dumpsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gille, 2010). For example, researchers have in their quest to understand landfills strongly contributed to consolidating the image of landfills as something negative (Paper II).…”
Section: The Perception Of Landfills As Dumpsmentioning
confidence: 99%
“…The sociologist Zuzan Gille (2010) has brought a socio-material perspective to waste studies, and demonstrated how social, technical, and material processes have changed the perception of waste in Hungary over time, and enlisted policies, cultures, economics, and technologies into various "waste regimes": the metallic regime, the efficiency regime and the chemical regime. Gille is mainly interested in different social institutions, following Young's (1982) understanding of resource regimes, such as the structure of rights, rules, and policies to regulate and govern the production and distribution of waste: "Waste regimes consist of social institutions and conventions that not only determine what wastes are considered valuable but also regulates their production and distribution" (Gille, 2013: 29).…”
Section: A Socio-materials Approach To Landfillsmentioning
confidence: 99%
See 3 more Smart Citations